2015
DOI: 10.4103/0973-1482.163851
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of invasive lobular carcinoma of the breast: A nationwide multicenter study in China

et al.

Abstract: ILC has a larger proportion of luminal A type compared with IDC. Larger sample size study for better known of molecular subtypes of ILC is needed in future to individualize the treatment decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Positive family history of breast cancer was present in 22.9% of cases. In contrast, a study conducted in 2015 on 135 cases of ILC reported only 4.5% of cases with positive family history 21 . This difference is possibly related to the small number of cases assessed in our study, leading to a biased sample.…”
Section: Discussionmentioning
confidence: 83%
“…Positive family history of breast cancer was present in 22.9% of cases. In contrast, a study conducted in 2015 on 135 cases of ILC reported only 4.5% of cases with positive family history 21 . This difference is possibly related to the small number of cases assessed in our study, leading to a biased sample.…”
Section: Discussionmentioning
confidence: 83%
“…[ 4 , 5 ] ILC tumors typically have a good prognosis, low histology grade, and positivity for the estrogen receptor; however, they can be strongly metastatic and are the main cause of cancer deaths among women in many countries worldwide. [ 2 , 6 ] There is increasing evidence that ILC is clinically unique, and that its early diagnosis and prognosis are especially important.…”
Section: Introductionmentioning
confidence: 99%